(untitled) (Revista Científica Integrada, 2023)
Aim: To identify the influence of urban parks on the quality of life and the characteristics of its users. Methods: This is a narrative review, carried out in the CAPES Journal Portal, SciELO and in the Virtual Health Library. To carry out the first selection of studies, the search words “urban parks” and “quality of life” were used. In this way, those that were published in the last five years and in any language were established for the inclusion of articles. As for the exclusion of articles, the established criteria were studies of literature reviews and articles prior to the year 2017. The data were analyzed according to the recommendations of qualitative studies, through discussion and synthesis, establishing the comparison between information and data from the literature. Results: Initially, 204 studies were found, of which 8 were selected to compose the final review version. The use of urban parks, whether for physical activity or leisure, may be related to the promotion of physical or mental health, as these spaces can be explored by any age group, although in the literature it has been revealed that young people use these spaces less. Conclusions: The use of urban parks is correlated with an improvement in the quality of life of users.